Culture Hero’s Intrepid Past (Prometheus, Loki, Syrdon… Coyote…) - Eloeva, Fatima; Sausverde, Erika (Literatūra, 2016)
The paper compares Loki of the Scandinavian and Syrdon of the Caucasian material (the Nart epic tradition) with the evolution of the character of Prometheus as described in the early texts (Theogony and Works and Days by Hesiod) and with his later transformation as described in Prometheus Bound by Aeschilus. This comparison makes it possible to demonstrate the general pattern of evolution which can be described as (chthonian) deity → trickster → culture hero. In this we do not agree with Eleazar Meletinskij’s statemwent, according to which the culture hero – Demiurge – is the most ancient character in the world folklore, while the trickster is a subsequent transformation of the image of the culture hero. Employing the Greek model (Hesiod’s Theogony) as our starting point, we will argue that an intriguer / a trickster is the most ancient mythological character, while the culture hero emerges as a result of later developments.
Keywords: trickster; culture hero; chthonian deity; metaphor; myth; comparative mythology; semantic evolution; idea of progress